Heterogeneous Immigrants and Foreign Direct Investment: The Role of Language Skills - Matthias Lücke; Tobias Stöhr (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We estimate a gravity model for bilateral FDI out-stocks from panel data for OECD reporting countries with bilateral and year fixed effects. With this demanding test, we find a robust positive effect of bilateral immigrants on bilateral FDI - provided that residents of the two countries have few language skills in common. We find a similar effect, in terms of size and statistical significance, for immigrants from third countries who speak the language(s) of the FDI host country. They thus are potential substitutes for bilateral migrants. A 1 percent increase in either immigrant group raises the FDI out-stock by 0.2 to 0.4 percent. Combined with various robustness checks, our findings suggest that immigrants facilitate outgoing FDI through their language skills, rather than through other characteristics like cultural familiarity. As most developing country residents have few language skills in common with rich country residents, developing country migrants in rich countries have a key role to play in facilitating FDI in their countries of origin.
Keywords: F21; F22; O14; 330